The effect of additives and mechanical agitation in surface modification of acrylic fibres by cutinase and esterase - Matamá, Maria Teresa (2006)
The surface of an acrylic fibre containing about 7% of vinyl acetate was modified using Fusarium solani pisi cutinase and a commercial esterase, Texazym PES. The effect of acrylic solvents and stabilising polyols on cutinase operational stability was studied. The half-life time of cutinase increased by 3.5-fold with the addition of 15% N,N-dimethylacetamide (DMA) and by 3-fold with 1M glycerol. The impact of additives and mechanical agitation in the protein adsorption and in the hydrolysis of vinyl acetate from acrylic fabric was investigated. The hydroxyl groups produced on the surface of the fibre were able to react specifically with Remazol Brilliant Blue R (cotton reactive dye) and to increase the colour of the acrylic-treated fabric. The best staining level was obtained with a high level of mechanical agitation and with the addition of 1% DMA. Under these conditions, the raise in the acrylic fabric colour depth was 30% for cutinase and 25% for Texazym. The crystallinity degree, determined by X-ray diffraction, was not significantly changed between control samples and samples treated with cutinase. The results showed that the outcome of the application of these enzymes depends closely on the reaction media conditions.